A simple equivalent plate model for dynamic bending stiffness of three-layer sandwich panels with shearing core. (26th May 2021) - Arasan, U.; Marchetti, F.; Chevillotte, F.; Jaouen, L.; Chronopoulos, D.; Gourdon, E.
Abstract: Equivalent or condensed plate models are being used in various industries to reduce the computation time in finite element modelling. Out of the available equivalent plate models, the model developed by J.L. Guyader in 1978 exhibits high agreement with Lamb wave theory but it requires some time for implementation. Therefore, in this paper, a simple model is proposed to quickly compute the dynamic equivalent parameters of a three-layer sandwich panel. Although the model is formulated from only four parameters, which could be easily computed via the asymptotic and transition behaviours of the sandwich panel, it is shown to be able to capture the equivalent dynamic response for the entire frequency range.